Shaping ability of different single-file rotary systems in simulated S-shaped canals by a new investigation approach: An in vitro study - Rami Kaddoura; Ahmad A Madarati; Mouhammad Al Tayyan (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aim of this study was to compare the shaping ability of single-file nickel-titanium systems in simulated S-shaped canals. Materials and Methods: Sixty simulated S-shaped canals were photographed and 12 levels along their length were determined. They were divided into four groups: A and B where the WaveOne Gold and Reciproc Blue reciprocating systems were used and Groups C and D for the OneCurve and Fanta-AF F-one rotary systems. Blocks were re-photographed and the before- and after-preparation photos were superimposed. Canals' widths were measured at each canal's level before and after preparation to calculate canals' deviations. The preparation times were recorded, and the data were analyzed by one-way ANOVA and Chi-square tests (P = 0.050). Results: The mean deviation in the middle third (0.14 mm) was greater than those in the coronal (0.08 mm) and apical thirds (0.09 mm) (P = 0.000). Furthermore, in this third, the OneCurve system caused the lowest greatest deviation (0.13 mm) but not different from the WaveOne Gold system (0.18 mm). At the apical third, the OneCurve showed the least mean deviation (0.07 mm) (P = 0.001) and the lowest mean of the greatest deviation (0.12 mm) (P = 0.000). Significantly, the highest percentage of the greatest deviations located within the canals' middle third (68.4%). The Fanta-AF-F-one and Reciproc Blue systems had higher percentages of the greatest deviation within the middle third (86.7% and 85.7%, respectively) than the OneCurve (42.9%) and WaveOne Gold systems (57.1%) (P = 0.013). The OneCurve and WaveOne Gold systems needed the least shaping times (57.15 and 63.07 s, respectively). Conclusions: The OneCurve system followed by the WaveOne Gold system had better shaping ability than other systems. The OneCurve and WaveOne Gold systems required shorter shaping times. The "greatest-deviation" can be more appropriate analysis than the mean deviation when the shaping ability is investigated.